Cu2+, Cr3+, and Ni2+ in mono- and multi-component aqueous solution adsorbed in passion fruit peels in natura and physicochemically modified: a comparative approach - Ramos, Bianca de Paula; Perez, Isadora Dias; Aliprandini, Paula; Boina, Rosane Freire [UNESP] (Springer Nature, 2022)
Among the low-cost adsorbent are agricultural residues, which can be used in natura or modified forms. This work evaluated the adsorption of Ni2+, Cu2+, and Cr3+ in mono- and multi-component aqueous solutions using passion fruit peels in natura (Nat-PF) and physicochemically modified (Mod-PF). The adsorption was investigated by kinetic and isotherm models. A comparative investigation was conducted to analyze the effect of the experimental conditions by statistical test, adsorption capacity ratio, selectivity of adsorbate, and distribution coefficient. In both adsorbents, the process occurs in monolayer by chemosorption. Equilibrium was reached after 30 min, with highest adsorption capacity for Cu2+ as 0.495 mg g−1, for Cr3+ as 0.483 mg g−1, and for Ni2+ as 0.464 mg g−1. The adsorption in Mod-PF was less affected in multi-component solutions, reducing the adsorption capacity by 0.06–0.15 times when compared to monocomponent solutions, while in Nat-PF a reduction of more than half of adsorption capacity was obtained. The modifications imposed on the biomass led to a change in its adsorptive selective, being Cr3+ > Cu2+ > Ni2+ for Nat-PF and Cu2+ > Ni2+ > Cr3+ for Mod-PF. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Activated carbon; Bioadsorbent; Metallic ions; Metals; Natural adsorbents; Residue; Wastewater